EFEKTIVITAS PROGRAM KAMPUNG KELUARGA BERENCANA (KB) DI DESA TEMBOAN KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - TESALONIKA SYELA MALEKE; MASJE PANGKEY; DEYSI TAMPONGANGOY (Sam Ratulangi University, 2022)
The purpose of this study was to determine and describe the effectiveness of the Family Planning Village(KB) Program in Temboan Village, Maesaan District, South Minahasa Regency. This research isdescriptive with a qualitative research approach. The data collection technique used is by observation orgoing directly to the field, interviews with research informants, and documentation of existing research.The theory used is the theory of Richard M. Steers regarding the measure of effectiveness and theindicators that influence effectiveness, namely goal achievement, integration, and adaptation. Based onthe results of existing research, it shows that the effectiveness of the Kampung KB Program in TemboanVillage, Maesaan District, South Minahasa Regency can be said to have been effective. However, thereare still some obstacles in the implementation of the Kampung KB program, namely Human Resources(HR) from some communities which are still lacking, resulting in a misunderstanding of the Kampung KBprogram, the socialization process is not yet mature in its preparation and implementation, and there arestill facilities. and infrastructure to be added. The suggestion from the researcher is to pay more attentionto the existing socialization process for more mature preparation and implementation so that thecommunity can understand correctly the KB Village program. As well as for the facilities andinfrastructure, it must be equipped so that the existing data can be pasted in the right place, namely MyData House.Keywords: Effectiveness, Family Planning Village Program, Community